The Groaning of Creation: Expanding our Eschatological Imagination Through the Paschal Mystery - King, Chelsea (Lumen et Vita, 2016)
One of the most difficult challenges facing belief in the Christian God is the problem of evil. How can there be a benevolent, omniscient, and omnipotent God, who allows pain, suffering and death in the world? Various theodicies have been constructed to address this question, and historically theologians have pointed to the Fall to explain such pain and suffering. However, theology in a post-evolutionary context is faced with a new challenge; the problem of pain and suffering is amplified by the millions of years of suffering and pain that have occurred before the advent of human beings. Today, the theologian must wrestle with the claim that pain, suffering, and death not only precedes human beings, but are in fact instruments in the very process of creation itself.